Connexin 43 signalling and cardioprotection. Issue 12 (30th December 2005) - Boengler, K; Schulz, R; Heusch, G
Abstract : Connexin (Cx) 43 is the predominant protein forming gap junctions and non-junctional hemichannels in ventricular myocardium. The Cx43 proteins are central to the cardioprotection afforded by ischaemic preconditioning (IP). The specific role of mitochondrial C×43 in protection by IP is reviewed.